Design of Strained Ge Schottky Diode on Si Substrate for Microwave Rectifier Circuit - Wei-Feng Liu; Xue-Mei Wu; Jian-Jun Song; Xin-Yan Zhao; Rong-Xi Xuan (Advances in Condensed Matter Physics)
In recent years, wireless energy transmission technology has developed rapidly and has received increasing attention in the industry. For microwave wireless energy transfer system applications, Ge Schottky diodes as the core components of the rectifier circuit are commonly used. Compared with Ge semiconductor, strained Ge semiconductor on Si substrate has the advantages of compatibility with Si process, low cost, and high electron mobility. It is an ideal replacement material for Ge semiconductor applications. In view of this, based on the model of the relationship between the performance of strained Ge semiconductor on Si substrate Schottky diodes and the geometric parameters of the device and the physical parameters of the material, Silvaco TCAD and ADS simulation software are jointly used to propose a novel strained Ge semiconductor on Si substrate Schottky diode for microwave rectification circuit. Simulation results show that the strained Ge semiconductor on Si substrate Schottky diode has a rectification efficiency of 70.1% when the input of the rectifier circuit is 20 dBm, the load resistance is R = 1000 Ω, and the load capacitance is C = 100 pF. Compared with traditional Ge Schottky diodes, this optimal operating point is closer to a low energy density, which is beneficial to a wide range of energy absorption. Studies have shown the feasibility of replacing Ge Schottky diodes. The research in this paper can provide valuable reference for the design and development of the core components of the rectifier circuit of the microwave infinite energy transmission system.